High‐throughput bioanalysis of sitagliptin in plasma using direct analysis in real time mass spectrometry and its application in the pharmacokinetic study thereof. Issue 2 (10th November 2021) - Liu, Yingze; Meng, Xiangjun; Zhang, Yuyao; Zhang, Linge; Shan, Yuqin; Gu, Jingkai; Sun, Dong
Abstract: Sitagliptin is a dipeptidyl peptidase‐IV inhibitor for the treatment of type 2 diabetes mellitus. In the present study, a sensitive and high‐throughput quantitative method based on the direct analysis in real time tandem mass spectrometry has been developed and validated for the bioanalysis of sitagliptin in rat plasma without chromatographic separation. Sitagliptin and its internal standard retagliptin were detected in positive ion mode by multiple reaction monitoring transitions at m/z 408.2→235.0 and 465.2→260.1, respectively. The method includes a simple solid‐phase extraction sample preparation procedure, through which appropriate and reproducible analytical results within the linear concentration range of 20–2000 ng/mL have been achieved. The intra‐ and interday precisions were <10.6% and the accuracies were ranging from −8.17 to 2.60%. This method has been successfully applied to the pharmacokinetic study of sitagliptin after single intravenous administration in rats. This approach shows considerable promise of direct analysis in real time tandem mass spectrometry method in the high‐throughput bioanalysis.